The historical place of the 'Friedman-Phelps' expectations critique. - Forder, J (Taylor and Francis, 2010)
The ‘expectations critique’, usually attributed to Friedman or Phelps and dated towards the end of the 1960s, in fact originates much earlier. And rather than being an insight properly attributable to a particular individual, it was, by that time, a commonplace of economic discussion. This much is easy to establish. It is argued that the common attribution arises at least in part because the Keynesians unwisely chose to express their disagreement with Friedman in terms of expectations rather than in terms of the existence of the natural rate of unemployment. As a result, forty years later, it has become hard to see that two separate points ever existed.